Fakto Yang Berhubungan Dengan Preeklampsia Pada Kehamilan Di RSU. Muhammadiyah Sumatera Utara Medan Tahun 2011-2012 - afni sucita resmi; Asfriyati ,MKes; Ria Masniari Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Preeclampsia is an illness marked with existing hypertension, proteinuria and edema as emerged long as inception or up to 48 hours post partum. This disorder shall take place on tri-semester III in inception. Preeclampsia is constitute one of causes to death of maternal in pregnancy beside blooding and infection. This study adopted an analytical descriptive method with a case control study which research aimed to determine factors correlating with the preeclampsia in Muhammadiyah Sumatera Utara general hospital for 2011-2012. The sample in case group are the pregnant maternal that has been diagnosed preeclampsia noted on medical record file and the sample on control group are those maternal in pregnancy that not be diagnosed with preeclampsia noted on medical record file. From the result of analysis with chi-square test has been obtained variable correlating with preeclampsia such as age (p=0.015), inception age (p-0.001), and variable not correlated such as Bad Obstetric History (BOH) (p=0.623), parity (p=0.076). From the result of analysis with multivariant the most dominant variable is inception age. The pregnant maternal is encouraged to have examination regularly to the public health service aimed to detect early the condition of his health in order to prevent any preeclampsia and to those paramedical is highly recommended provide counseling to those pregnant maternal to enrich their knowledge about preeclampsia disorder so that the mortality on maternal and mortality upon babies shall decrease down. Keywords: Preeclampsia, age, Bad Obstetric History, parity